Mapping Islamic banking and sustainable development research: A Scopus-based bibliometric and VOSviewer keyword co-occurrence cluster analysis (2008–2024) - Garbo, Anom; Hasanah, Shofia Mauizotun (Journal of Islamic Economics Lariba, 2025)
IntroductionSustainable development has become a central paradigm in contemporary finance, shaping how banking institutions align capital allocation, governance, and social value creation with long-term development goals. Within this context, Islamic banking is increasingly examined as a values-driven system that may support sustainable development through ethical foundations, Sharia compliance, and inclusion-oriented financial practices. However, the expanding literature remains fragmented across themes, methods, and policy debates, creating a need for systematic mapping of its intellectual structure and research frontiers.ObjectivesThis study aims to (1) map the evolution and distribution of research on Islamic banking and sustainable development, (2) identify dominant and emerging thematic clusters through keyword co-occurrence, and (3) highlight research gaps and future directions that can inform theory development, banking practice, and sustainability-oriented policy.MethodThis study employs a bibliometric approach using Scopus metadata retrieved through the query (TITLE-ABS-KEY ( islamic AND bank ) AND TITLE-ABS-KEY ("sustainable development")) AND PUBYEAR > 2007 AND PUBYEAR < 2025, producing 120 documents. Keyword co-occurrence cluster analysis was conducted in VOSviewer with the following settings: type of analysis co-occurrence, unit of analysis all keywords, and minimum keyword occurrence of two. Of 602 keywords, 95 met the threshold. The thematic structure was interpreted using network visualization, overlay visualization, and density visualization.ResultsThe findings show that “sustainable development” functions as the most central and highly connected concept, indicating its role as the primary thematic anchor of the literature. The network structure reveals multiple interconnected streams, including (1) corporate social responsibility, Sharia-aligned environmental, social, and governance, governance mechanisms, and bank performance; (2) sustainable development goals, poverty, financial inclusion, and Islamic social finance; and (3) methodological diversification combining econometric modeling and qualitative inquiry. Overlay patterns suggest a shift from earlier governance and performance-focused studies toward more recent emphasis on sustainable development goals, inclusion, and innovation.ImplicationsThe study provides evidence that sustainability in Islamic banking research is increasingly institutionalized through governance and reporting pathways while expanding toward inclusion-driven development agendas. These insights support more coherent research agendas, improved sustainability governance practices, and policy frameworks that strengthen Sharia-aligned environmental, social, and governance integration and social finance effectiveness.Originality/NoveltyThis study offers a systematic, data-driven synthesis of the Islamic banking–sustainable development research domain by integrating bibliometric indicators with keyword co-occurrence clustering and multi-layer visualization, enabling clearer identification of thematic concentration, emerging priorities, and underexplored research frontiers.